Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the system of equations, we need to find the points [tex]\((x, y)\)[/tex] that satisfy both equations:
[tex]\[ y = 2x \][/tex]
[tex]\[ y = x^2 - 8 \][/tex]
We start by substituting [tex]\( y \)[/tex] from the first equation into the second equation because both are equal to [tex]\( y \)[/tex].
[tex]\[ 2x = x^2 - 8 \][/tex]
Next, we rearrange this equation to form a standard quadratic equation:
[tex]\[ x^2 - 2x - 8 = 0 \][/tex]
To solve the quadratic equation, we can factorize:
[tex]\[ x^2 - 2x - 8 = (x - 4)(x + 2) = 0 \][/tex]
Setting each factor to zero gives us the roots of the equation:
[tex]\[ x - 4 = 0 \implies x = 4 \][/tex]
[tex]\[ x + 2 = 0 \implies x = -2 \][/tex]
Now, we substitute each value of [tex]\( x \)[/tex] back into the first equation [tex]\( y = 2x \)[/tex] to find the corresponding [tex]\( y \)[/tex] values.
For [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 2(4) = 8 \][/tex]
So one solution is [tex]\((4, 8)\)[/tex].
For [tex]\( x = -2 \)[/tex]:
[tex]\[ y = 2(-2) = -4 \][/tex]
So another solution is [tex]\((-2, -4)\)[/tex].
Thus, the solutions to the system of equations are:
[tex]\[ (-2, -4) \text{ and } (4, 8) \][/tex]
From the given choices, the correct option is:
C. [tex]\((-2, -4)\)[/tex] and [tex]\((4, 8)\)[/tex]
[tex]\[ y = 2x \][/tex]
[tex]\[ y = x^2 - 8 \][/tex]
We start by substituting [tex]\( y \)[/tex] from the first equation into the second equation because both are equal to [tex]\( y \)[/tex].
[tex]\[ 2x = x^2 - 8 \][/tex]
Next, we rearrange this equation to form a standard quadratic equation:
[tex]\[ x^2 - 2x - 8 = 0 \][/tex]
To solve the quadratic equation, we can factorize:
[tex]\[ x^2 - 2x - 8 = (x - 4)(x + 2) = 0 \][/tex]
Setting each factor to zero gives us the roots of the equation:
[tex]\[ x - 4 = 0 \implies x = 4 \][/tex]
[tex]\[ x + 2 = 0 \implies x = -2 \][/tex]
Now, we substitute each value of [tex]\( x \)[/tex] back into the first equation [tex]\( y = 2x \)[/tex] to find the corresponding [tex]\( y \)[/tex] values.
For [tex]\( x = 4 \)[/tex]:
[tex]\[ y = 2(4) = 8 \][/tex]
So one solution is [tex]\((4, 8)\)[/tex].
For [tex]\( x = -2 \)[/tex]:
[tex]\[ y = 2(-2) = -4 \][/tex]
So another solution is [tex]\((-2, -4)\)[/tex].
Thus, the solutions to the system of equations are:
[tex]\[ (-2, -4) \text{ and } (4, 8) \][/tex]
From the given choices, the correct option is:
C. [tex]\((-2, -4)\)[/tex] and [tex]\((4, 8)\)[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.